(untitled) (Research, Society and Development, 2021)
This study aims to verify and analyze the articles produced in the scientific literature that discuss the theme in national journals and to analyze nursing care related to the care in child population with parasites. This is an integrative literature review using the LILACS (Latin American and Caribbean Literature in Health Sciences), SciELO (Scientific Electronic Library Online) and BDEnf databases, published in Portuguese from 2010 to 2020. From the data search, 10 articles were used to compose the discussion, 3 articles from LILACS, 5 from SciELO and 2 from BDEnf. The riverside child population is more unprotected from infection by parasites due to the precariousness of basic sanitation in the region, in addition to cultural factors of food and personal hygiene, thus, nursing care has an essential role in promoting the prevention and treatment of these diseases, in order to ensure health and well-being for children.